Bouncers: Violence and Governance in the Night-time Economy - Hobbs, Dick; Hadfield, Philip; Lister, Stuart; Winlow, Simon (Oxford University Press, 2003)
"In recent years, the expansion of night-time leisure has emerged as a key indicator of post-industrial urban prosperity, attracting investment, creating employment and re-generating the built environment. These leisure economies are youth-dominated, focusing upon the sale and consumption of alcohol. Unprecedented numbers of young people now flock to town centres that are crammed with bars, pubs and clubs, and the resulting violent disorder has over-run police resources that remain geared to the drinking patterns and alcohol cultures of previous generations. Post-industrial re-structuring has spawned an increasingly complex mass of night-time leisure options through which numerous licit and illicit commercial opportunities flow. Yet, regardless of the fashionable and romantic notions of many contemporary urban theorists, it is alcohol, mass intoxication and profit rather than 'cultural regeneration,' which lies at the heart of this rapidly expanding dimension of post-industrial urbanism. Private security in the bulky form of bouncers fills the void left by the public police. These men (only 7% are women), whose activities are barely regulated by the State, are dominated by a powerful subculture rooted in routine violence and intimidation. Using ethnography, participant observation and extensive interviews with all the main players, this book charts the emergence of the bouncer as one of the most graphic symbols in the iconography of post-industrial Britain." Argumentaire de l'ouvrage.
Keywords: Law / International